The Importance of Needs Analysis for English for Specific Purposes at Elementary School Teacher Department of University of Muhammadiyah Sukabumi - Amalia, Arsyi Rizqia (UICELL, 2017)
Based on a data, there are several elementary schools in Sukabumi which do not have a teacher with English background education, so that the graduate of elementary school teacher education or PGSD who is teaching English in the school. This research is conducted on PGSD students of University of Muhammadiyah Sukabumi (UMMI) to prepare themselves as teachers of English in the future, but it is found that students at PGSD UMMI have difficulties in following the lessons taught on campus. The objectives of this research are (1) to know the background of studentsâ English competency as need analysis process. (2) to make an appropriate materials that is given in ESP subjects. The researcher conducted this study with quantitative and RnD methods. The results of this study show that (1) more than 90% of students are not able to pronounce letters and to mention numbers, especially large numbers in English correctly; (2) the impact of the research is the change of syllabus where the materials taught to the students. From this research, it can be concluded that need analysis is something that must be done to improve the quality of English education in our environment.